The G2019S Mutation in LRRK2 Imparts Resiliency to Kinase Inhibition - Kelly, Kaela (Exp Neurol, 2018)
The G2019S mutation in LRRK2 is one of the most common known genetic causes of neurodegeneration and Parkinson disease (PD). LRRK2 mutations are thought to enhance LRRK2 kinase activity. Efficacious small molecule LRRK2 kinase inhibitors with favorable drug properties have recently been developed for pre-clinical studies in rodent models, and inhibitors have advanced to safety trials in humans. Rats that express human G2019S-LRRK2 protein and G2019S-LRRK2 knock-in mice provide newly characterized models to better understand the ostensible target for inhibitors. Herein, we explore the relationships between LRRK2 kinase inhibition in the brain and the periphery to establish the link between LRRK2 kinase activity and protein stability, induction of lysosomal defects in kidney and lung, and how G2019S-LRRK2 expression impacts these phenotypes. Using a novel ultra-sensitive scalable assay based on protein capillary electrophoresis with LRRK2 kinase inhibitors included in-diet, G2019S-LRRK2 protein was resilient to inhibition compared to wild-type (WT)-LRRK2 protein, particularly in the brain. Whereas WT-LRRK2 kinase activity could be completed blocked without lowering LRRK2 protein levels, higher inhibitor concentrations were necessary to fully reduce G2019S-LRRK2 activity. G2019S-LRRK2 expression afforded robust protection from inhibitor-induced kidney lysosomal defects, suggesting a gain-of-function for the mutation in this phenotype. In rodents treated with inhibitors, parallel measurements of phospho-Rab10 revealed a poor correlation to phospho-LRRK2, likely due to cells that express Rab10 but poorly express LRRK2 in heterogenous tissues and cell isolates. In summary, our results highlight several challenges associated with the inhibition of the G2019S-LRRK2 kinase that might be considered in initial clinical efforts.